2020
DOI: 10.1519/jsc.0000000000003785
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Session-RPE and External Measures of Training Load in Youth Soccer Training

Abstract: Marynowicz, J, Kikut, K, Lango, M, Horna, D, and Andrzejewski, M. Relationship between the session-RPE and external measures of training load in youth soccer training. J Strength Cond Res 34(10): 2800–2804, 2020—The aim of this study was to identify the external training load (TL) markers (10 Hz Global Positioning System) that are most influential on the rating of perceived exertion (RPE) and session-RPE (sRPE) during youth soccer training. Data were collected from 18 youth soccer players during an 18-week in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
5
25
3
Order By: Relevance
“…Kelly et al [65] indicated correlation between changes in sRPE and Edwards TRIMP (r = 0.75, p < 0.05). Particularly, these main findings prove that there were correlation changes between perceived exertion and HR measures for elite female [52], semi-professional [115], elite/professional [50,65], and young amateurs [53,98].…”
Section: Relationships Between Weekly Internal and External Loadmentioning
confidence: 53%
See 2 more Smart Citations
“…Kelly et al [65] indicated correlation between changes in sRPE and Edwards TRIMP (r = 0.75, p < 0.05). Particularly, these main findings prove that there were correlation changes between perceived exertion and HR measures for elite female [52], semi-professional [115], elite/professional [50,65], and young amateurs [53,98].…”
Section: Relationships Between Weekly Internal and External Loadmentioning
confidence: 53%
“…The internal measures had correlation with volume of HSR and sprinting (r = 0.40 to 0.67; p < 0.01). Marynowicz et al [98] reported a large and positive within-individual correlations for total distance, PL, number of ACC, and sRPE (r = 0.70, 0.64, and 0.62, respectively, p < 0.001). Small to moderate within-individual correlations were noted between RPE and measures of intensity (r = 0.16 to 0.39).…”
Section: Relationships Between Weekly Internal and External Loadmentioning
confidence: 96%
See 1 more Smart Citation
“…The accumulated training load and the seasonal variation in the different stages of developments still constitute a research hot topic concerning youth football. Additionally, the sRPE provided consistent information about internal training throughout an entire season [15,61]. No significant differences were found in the TQR score for inter-week analysis.…”
Section: Inter-week Analysismentioning
confidence: 84%
“…Validity and reliability of RPE are well established in several sports and physical activities at different ages and expertise levels [14]. The session rating of perceived exertion (sRPE) has been reported as a better training load indicator to explain the training session intensity in comparison to RPE [15].…”
Section: Introductionmentioning
confidence: 99%